Molecular and biochemical characterization of rice pectin methylesterase inhibitors (OsPMEIs) - Nguyen, Hong Phuong (Plant physiology and biochemistry : PPB, 2016)
Copyright © 2016 Elsevier Masson SAS. All rights reserved.